Synovial cysts of the hip. - Angelini, Andrea; Zanotti, Gabriele; Berizzi, Antonio; Staffa, Guido; Piccinini, Elio; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2018)
Background: Synovial cysts of the hip are relatively rare lesions comparing to other joints. Patients are usually asymptomatic, but in some cases symptoms such as pain and/or compression of vessels or nerve could be present. Purpose of the study was to define clinical features and optimal management of synovial cyst of the hip joint through an accurate review of the literature. Methods: We present three consecutive cases treated with three different therapeutic strategies: surgical excision, wait-and-see and needle aspiration. An accurate review of the literature has been performed to identify patients who had been treated for synovial cyst of the hip. Results: Due to the rarity of the disease, there are no significant data in literature supporting the gold standard of treatment. Treatment of the synovial cyst depends on their size, symptoms and comorbidities. Conclusions: Most of the Authors recommend surgical treatment for symptomatic synovial cysts and needle aspiration as an option treatment in asymptomatic patients without vessel or nerve compression. In patients that referred symptoms in correspondence with the hip joint, not strictly related with radiograph findings, a CT or MRI examinations should be performed to exclude possible differential diagnosis.